Piezoelectric properties of PVDF‐TrFE/BaTiO3 composite foams with different contents of TrFE units - Kubin, Mateja; Makreski, Petre; Zanoni, Michele; Selleri, Giacomo; Gasperini, Leonardo; Fabiani, Davide; Gualandi, Chiara; Bužarovska, Aleksandra (Wiley, 2023)
AbstractPiezoelectric (PE) materials play an important role in the emerging field of micro and wearable electronics. Achieving high PE response is a key feature for their use in energy harvesting and sensing systems. In this study, highly porous lightweight composite foams composed of PVDF‐TrFE (70/30 and 80/20 mol%) and different BaTiO3 content (5, 10, and 20 wt%) are prepared by thermally induced phase separation method. The PE foams were structurally and thermally examined by using Fourier‐transform infrared spectroscopy, x‐ray diffraction, differential scanning calorimetry, and thermogravimetric analysis analyses. All composite foams were characterized by high β‐phase content, while the addition of ceramic particles resulted in higher crystallinity and thermal stability of the investigated foams. Two distinct poling methods were employed due to the different molar compositions of the copolymers. The PE response was measured by the PE strain coefficient (d33) and the output current (Ip). The composite foams based on PVDF‐TrFE 70/30 mol% copolymer, having two well‐separated Curie temperatures for the organic and inorganic phases, can be polarized to achieve the contribution of both components to the PE performance, reaching the highest value of −28.3 pC N−1 and 130 nA at 10 Hz for the composite with 20 wt% BaTiO3.